ENVIRONMENTAL AUDIT SYSTEM FOR PROTECTION OF THE RIGHT TO A GOOD ENVIRONMENT AS REVIEWED FROM LAW NUMBER 32 OF 2009 CONCERNING ENVIRONMENTAL PROTECTION AND MANAGEMENT IN INDONESIA - Muhammad Endang Sudrajat; Ikomatussuniah Ikomatussuniah; Mas Iman Kusnandar; Firdaus Firdaus; Rani Sri Agustina (Universitas Dharmawangsa Medan, 2026)
The environmental audit system serves as a tool to protect the right to a healthy environment, as mandated by Law Number 32 of 2009 concerning Environmental Protection and Management. This includes the declining quality of the environment in Indonesia, which has an impact on public welfare. This study aims to evaluate the effectiveness of the implementation of the environmental audit system and ensure the protection of the right to a healthy environment. The research framework is based on the theory of environmental auditing and sustainable development, with a normative and empirical juridical approach. The implementation of environmental audits highlights the role of regulations, implementation constraints, and their impact on sustainable development. Environmental audits have been shown to encourage compliance with regulations, identify environmental risks, and provide recommendations for improving environmental management. However, obstacles remain, such as a lack of auditor capacity, misalignment between rules and practices, and low transparency in reporting. Recommendations include strengthening regulations, community engagement, and adopting technology to increase transparency and accountability. This document concludes that environmental audits play a crucial role in protecting the community's right to a healthy environment and supporting the Sustainable Development Goals. Key recommendations include strengthening the legal framework, increasing auditor capacity, and actively engaging the community in environmental oversight. With effective implementation, the environmental audit system can become a strategic instrument to maintain the quality of life of the community and the sustainability of ecosystems in Indonesia.